2015
DOI: 10.1159/000430334
|View full text |Cite
|
Sign up to set email alerts
|

Role for HIF-1α and Downstream Pathways in Regulating Neuronal Injury after Intracerebral Hemorrhage in Diabetes

Abstract: This is an Open Access article licensed under the terms of the Creative Commons AttributionNonCommercial 3.0 Unported license (CC BY-NC) (www.karger.com/OA-license), applicable to the online version of the article only. Distribution permitted for non-commercial purposes only.Copyright © 2015 S. Karger AG, Basel Key Words Intracerebral hemorrhage • HIF-1α • VEGF • DiabetesAbstract Background/Aims: HIF-1α is accumulated in the cellular nucleus and cytoplasm under conditions of oxygen deprivation and engaged in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Also, VEGF and its subtype receptor VEGFR-2 play an important role in pathologic angiogenesis [32, 33]. Amplified HIF-1α, VEGF and VEGFR-2 have been found in the brain tissues after induction of ICH and promotion of VEGF and VEGFR-2 by stabilization of HIF-1α can improve neurological deficits and increased brain water content induced by ICH [18]. Nevertheless, results of our current study provide evidence that blocking of mTOR signal plays a beneficial role in modulating brain injuries observed in ICH via VEGF mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Also, VEGF and its subtype receptor VEGFR-2 play an important role in pathologic angiogenesis [32, 33]. Amplified HIF-1α, VEGF and VEGFR-2 have been found in the brain tissues after induction of ICH and promotion of VEGF and VEGFR-2 by stabilization of HIF-1α can improve neurological deficits and increased brain water content induced by ICH [18]. Nevertheless, results of our current study provide evidence that blocking of mTOR signal plays a beneficial role in modulating brain injuries observed in ICH via VEGF mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanations with regard to the role hyperglycemia plays in poor outcome after ICH were stated in several previous reports [1315,17,20], but the definite molecular mechanism remains to be elucidated [23,24]. Experimental studies showed that diffuse brain edema, perihematomal increased neuronal apoptosis, and reduced autophagy, as well as larger hematoma formation, were caused by hyperglycemia after ICH [2527].…”
Section: Discussionmentioning
confidence: 99%
“…Also, VEGF and its subtype receptor VEGFR-2 play an important role in pathologic angiogenesis [ 20 , 21 ]. Amplified HIF-1α, VEGF and VEGFR-2 have been found in the brain tissues after induction of CA and promotion of VEGF and VEGFR-2 by stabilisation of HIF-1α can improve neurological deficits and increased brain water content induced by ICH [ 22 ]. Nevertheless, results of our current study provide evidence that blocking of mTOR signal plays a beneficial role in modulating brain injuries observed in CA rats via VEGF mechanisms.…”
Section: Discussionmentioning
confidence: 99%